PENGARUH KUALITAS E-GOVERNMENT TERHADAP KEPUASAN PENGGUNA E-FILING: STUDI KASUS WAJIB PAJAK DI SURAKARTA - Gunawan Setyo Utomo; Kartika Hendra Titisari; Anita Wijayanti (Universitas Medan Area, 2020)
This study aims to determine the effect of system quality, information quality, and service quality on E-filing user satisfaction in Surakarta. The population and sample in this study are individual taxpayers registered at the Pratama Surakarta Tax Office in 2019. The data collection technique of this study uses incidental sampling techniques, and the determination of the number of samples using Slovin formula with a sample of 100 respondents. The data used in this study is a questionnaire using a Likert scale. The data analysis technique used in this study is multiple linear regressions. The results showed the analysis there is a positive influence on system quality and service quality on E-filing user satisfaction. While the quality of the information does not affected E-filing user satisfaction.